Soft Power and Rehabilitation Centers in The United Arab Emirates - Alyassi, Marwan; Alomosh, Ahmad (Al-Adab Journal, 2026)
This study aims to explore soft power and rehabilitation centers by highlighting violent extremism and the importance of soft power in the security and educational sectors. It also analyzes the soft power of the United Arab Emirates. The study concluded by emphasizing the importance of rehabilitation centers as a form of soft power in reducing violent extremism, as well as highlighting the role of the UAE in combating violent extremism.